CURRENT STATUS OF HEALTH EDUCATION ACTIVITIES FOR SURGICAL PATIENTS BY NURSES AND ASSOCIATED FACTORS AT HAI DUONG GENERAL HOSPITAL, VIETNAM, IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To survey the current status of health education activities and some factors related to nurses’ health education at Hai Duong General Hospital, based on feedback from surgical patients in 2024.Methods: A cross-sectional descriptive study was conducted on 190 surgical patients from four surgical departments at Hai Duong Provincial General Hospital from November 2024 to December 2024. The status of health education activities, as perceived by patients, was assessed using 42 yes/no questions on health education content at three key time points: preoperative, postoperative, and pre-discharge. Each “yes” response was scored as 1 point.Results: The proportions of patients who received health education counseling from nurses at the three time points were: 83.7% before surgery, 48.4% after surgery, and 58.4% before discharge. A total of 60% of patients reported receiving adequate health education at all three stages. Factors associated with nurses’ health education activities included the number of hospital admissions and the patient's history of previous surgeries.Conclusion: Only 60% of surgical patients reported receiving complete health education at all three key time points. It is necessary to strengthen health education activities, particularly in the postoperative period and prior to discharge.
Keywords: health education, surgical patients, Hai Duong General Hospital.